Trends of Clinical Research on Facial Spasm in Korean Medicine: A Review of Case Studies - Hea Sun Chun; Ju Chul Kim (MEDrang Inc., 2023)
This review aimed to examine and analyze trends of clinical research using case studies on facial spasms in Korean medicine. Seven web databases were searched for case studies on facial spasms using Korean and English search terms. Case studies were selected using the exclusion and inclusion criteria. Overall, 13 case studies were selected, analyzed, and classified according to the publication year and journal, study participants, cause, treatment methods, pattern identification, evaluation methods, improvement, and side effects. Case studies reporting on various treatment methods in Korean medicine, including acupuncture and pharmacopuncture for facial spasms, have been published since 2000. In addition, studies on new treatment methods in Korean medicine for facial spasm have been published. Combination therapy is the most common method used in Korean medicine-based case studies; therefore, future studies on single treatment are necessary. Most of the case studies on Korean medicine reported improved symptoms and patient satisfaction with the Korean medicine treatment method. No side effects were reported, except for facial swelling and bruising, indicating that Korean medicine treatment methods for facial spasm were safe and effective. Therefore, the Korean medicine treatment methods for facial spasm can be actively used in clinical practice and future research.